The Development and Potential Evaluation of Indonesian Lore Lindu National Park Ecotourism in Relation to the Economic Growth of the Surrounding Community - MANURUNG, Konder; BASIR-CYIO, Muhammad; BASRI, Hasan; EFFENDY, EFFENDY (Journal of Environmental Management and Tourism, 2019)
The irresponsible utilization of natural resources in the Lore Lindu National Park (LLNP) could damage the sustainability of the ecosystem. One of the methods of natural resources utilization of LLNP was Ecotourism. Ecotourism was one of the approaches that kept in mind socio-economic aspects. This research used cross-sectional data and data collection was conducted from March until June 2018. The location of this research was the area of LLNP located in the administrative area of Sigi Regency. The research was conducted across eight villages in Sigi Regency; the number of respondents used was 284 households head (HH). Data collection and data analysis employed questionnaires and structural equation modeling (SEM) respectively. The results of this research showed that there was a positive and significant relationship between the utilization of forest products for household industry, the ecology utilization of the rebuttal area, socio-cultural community, and institutional availability with the economic growth of the surrounding community of LLNP. The strongest relationship was between the utilization of ecology in the rebuttal area of LLNP and the economic growth of the surrounding community. The development potential of LLNP ecotourism could be improved by utilizing forest products for household industry, utilizing the ecology of the rebuttal area of LLNP, increasing the socio-cultural relationship of the surrounding community, and enhancing institutional functions.